“É um Plano Diretor ou plano destruidor?”: disputas discursivas sobre o Plano Diretor da cidade de São Luís - MA - MALHEIROS, Aerica Souza (2022)
This work aims to analyze the discursive disputes raised by the revision of the Plan Director of the city of São Luís, MA. In this way, it seeks to examine the performance of entities and institutions that influence the process of reviewing the Plan Director and the “city models” defended. Agents and groups inserted in social segments are identified and I observe how the defense of its material interests is reflected in the city through the strategies adopted. Based on the empirical clipping made, the public hearings organized by the City Council in 2019 were examined, during which agents fight for the ideals they intend to implement. It is a political game, built with discursive exchanges, in which alliances are formed. The present work therefore focuses on the process of reviewing the Plan Director and political organizations in the use of urban policy in the city.